РАННЯЯ ДИАГНОСТИКА АТЕРОСКЛЕРОЗА СОННЫХ АРТЕРИЙ У БОЛЬНЫХ РЕВМАТОИДНЫМ АРТРИТОМ - E. R. Sagitova; G. G. Bagirova (Klinicist, 2014)
Aim — to estimate informing of different risk factors predisposing to development of carotid atherosclerosis and possibility of its prognostication in patients with rheumatoid arthritis (RA).Materials and methods. 100 patients with RA were examined. Age of patients was 53.4 ± 10.1 years. Clinical examination included conventional methods of research in rheumatology. Doppler ultrasound was carried of the brachiocephalic vessels.Results. The degree of severity of atherosclerotic changes in carotid arteries varied among different patients and more occurs in the elderly,with higher activity and severity of the process. Vascular lesions often are identified using instrumental methods than manifested clinically.Conclusion. Atherosclerosis of varying severity was observed in 80 % of RA patients. Changes in them do not depend on gender, duration of RA. There were a significant increase of the age, increased activity of the process and the index of severity.